Epidemiologic Study of Enterobius vermicularis Infection among Schoolchildren in the Republic of Marshall Islands. (2nd August 2021) - Fan, Chia-Kwung; Sonko, Pasaikou; Lee, Yueh-Lun; Yin, Ai-Wen; Chuang, Ting-Wu; Kios, Ramson; Wang, Ying-Ting; Chou, Chia-Mei; Hsu, Shao-Lun; Wu, Mai-Szu; Lin, Jia-Wei; Tu, Chia-Ying
Abstract : The prevalence and risk factors of Enterobius vermicularis (pinworm) infection among primary schoolchildren (PSC) in the Marshall Islands remain unknown; thus, investigation on the status of pinworm infection rate is necessary to establish baseline data. After parents'/guardians' consent, a total of 346 children (179 boys and 167 girls) participated in this study. Individual's perianal area and thumbs were inspected by using the Scotch tape technique and cellophane tape method, respectively. For each child, demographic and risk factor data were collected by a structured questionnaire and statistically analyzed. The overall prevalence of pinworm infection was 12.14% (42/346). Univariate analysis indicated significant differences in PSC who live in an urban area compared to those who live in the rural area p = 0.01 . Multivariate analysis still found that PSC who live in the rural area had higher chances to acquire pinworm infection. However, no risk factors were identified to be associated with personal hygiene, sibling number, and parent's educational level or occupation. Nevertheless, a pinworm-like egg was detected on the thumb of one male participant. Children living in the rural area and thumb-sucking behavior are two of the important risk factors of transmitting pinworm infection in the PSC in the Marshall Islands. We suggested an urgent and continuous provision of adequate hygienic sensitization in the school and the community.